Modulation of Dormancy and Growth Responses in Reproductive Buds of Temperate Trees - Lloret, Alba; Badenes, María Luisa; Ríos, Gabino (Frontiers in Plant Science, 2018)
During autumn perennial trees cease growth and form structures called buds in order to protect meristems from the unfavourable environmental conditions, including low temperature and desiccation. In addition to increased tolerance to these abiotic stresses, reproductive buds modulate developmental programmes leading to dormancy induction to avoid premature growth resumption, and flowering pathways. Stress tolerance, dormancy and flowering processes are thus physically and temporarily restricted to a bud, and consequently forced to interact at the regulatory level. We review recent genomic, genetic and molecular contributions to the knowledge of these three processes in trees, highlighting the role of epigenetic modifications, phytohormones, and common regulatory factors. Finally, we emphasise the utility of transcriptomic approaches for the identification of key structural and regulatory genes involved in bud processes, illustrated with our own experience using peach as a model.